Measurement of Bank Service Performance Using Bank Service Quality Index - Yeni Guspita Sari; Firman Firman (Jurnal Praktik Bisnis, 2019)
The purpose of this study is to determine the level of service performance by using The Bank Service Quality Index at the Bank Nagari Branch at Universitas Negeri Padang. The study population is all customers of Bank Nagari Branch at UNP and sample of 310 people. Based on factor analysis, six factors were obtained to measure bank performance, namely: realization, service portfolio, and reliability; access; price; guarantee; empathy; and effectiveness are sorted by the importance of each dimension. The results also show that the performance of Bank Nagari Branch at UNP based on BSQ Index of 3.7 indicating that its performance is good enough.